The Post-Crisis Slump in the Euro Area and the US: Evidence from an Estimated Three-Region DSGE Model - Lukas Vogel; Robert Kollmann; Beatrice Pataracchia; Marco Ratto; Werner Roeger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The global financial crisis (2008-09) led to a sharp contraction in both Euro Area (EA) and US real activity, and was followed by a long-lasting slump. However, the post-crisis adjustment in the EA and the US shows striking differences—in particular, the EA slump has been markedly more protracted. We estimate a three-region (EA, US and Rest of World) New Keynesian DSGE model (using quarterly data for 1999-2014) to quantify the drivers of the divergent EA and US adjustment paths. Our results suggest that financial shocks were key drivers of the 2008-09 Great Recession, for both the EA and the US. The post-2009 slump in the EA mainly reflects a combination of adverse aggregate demand and supply shocks, in particular lower productivity growth, and persistent adverse shocks to capital investment, linked to the continuing poor health of the EA financial system. Adverse financial shocks were less persistent for the US. The dynamics of financial shocks identified by the model is consistent with observed performance indicators of the EA and US banking systems.
Keywords: E32; F41; C11; 330